Path to publication: A peer mentorship model for student-lead surgical research - Waqar, Usama; Hareem Rauf; Muskaan Abdul Qadir; Hina Inam (Journal of the Pakistan Medical Association, 2022)
Early and sustained involvement in research is imperative for medical students to ensure better career prospects in addition to provision of high-quality, evidence-based care to patients. However, involvement of students in surgical research still remains limited, owing to inadequate research training. The current paper was planned to describe the structure of the "Path to Publication" series, incorporating peer mentorship with capacity-building research workshops for medical students. A total of 25 students were grouped into 8 surgical subspecialty groups to conduct research, supervised by experienced student research and faculty mentors. In addition, a series of research workshops were organized in synchronization with the different phases of research for all groups, equipping medical students with the necessary skills needed for each phase. Continuous...